Metabolic control in type 2 diabetes correlates weakly with patient adherence to oral hypoglycaemic treatment. - Loke, Seng Cheong; Jong, Michelle (Academy of Medicine, Singapore, 2008)
Introduction: Patient adherence to treatment is viewed as essential to good metabolic control in diabetes. Our primary objective was to determine if self-reported patient adherence correlated strongly with metabolic control. Our secondary objective was to determine the natural grouping of factors which influence adherence.